1997
DOI: 10.1017/s0043174500092808
|View full text |Cite
|
Sign up to set email alerts
|

Giant foxtail (Setaria faberi) interference in nonirrigated corn (Zea mays)

Abstract: Studies were conducted at East Lansing, MI, in 1994 and 1995 to examine corn yield response to giant foxtail interference and to examine the effect of giant foxtail density on giant foxtail biomass, seed production, and seed germination. Treatments consisted of 0, 10, 30, 60, 84, and 98 giant foxtail plants m−1of row in 1994 and 0, 10, 27, 30, 60, and 69 plants m−1of row in 1995. The influence of giant foxtail density on corn yield fit a hyperbolic equation. Corn yields were reduced 13% in 1994 and 14% in 1995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…Bosnic and Swanton (1997) reported that barnyardgrass at 39 plants m −2 reduced corn yield by 14% when they emerged at the 3‐leaf corn stage as compared with 4% at the 7‐leaf stage. In Michigan, Fausey et al (1997) reported that corn grain yields were reduced by up to 14% by 13 giant foxtail plants m −2 germinating 2 d after corn emergence.…”
Section: Resultsmentioning
confidence: 99%
“…Bosnic and Swanton (1997) reported that barnyardgrass at 39 plants m −2 reduced corn yield by 14% when they emerged at the 3‐leaf corn stage as compared with 4% at the 7‐leaf stage. In Michigan, Fausey et al (1997) reported that corn grain yields were reduced by up to 14% by 13 giant foxtail plants m −2 germinating 2 d after corn emergence.…”
Section: Resultsmentioning
confidence: 99%
“…Knake and Slife (1962) reported 25% yield loss caused by more than 150 giant foxtail plants m-1 row across 3 yr in Illinois. Giant foxtail at greater than 100 plants m-1 row resulted in 40% yield loss in Michigan (Fausey et al 1997). In contrast, Langton and Harvey (1994) reported that 168 giant foxtail plants m-1 row did not cause yield loss in an experiment in Wisconsin.…”
mentioning
confidence: 97%
“…Weed species, densities, and their interactions influence maize yield loss [49,50]. Weed plants compete with maize for their essential growth resources like water, nutrients, space etc.…”
Section: The Critical Period Of Crop-weed Competitionmentioning
confidence: 99%